WVJ 2022
DOI: 10.54203/scil.2022.wvj53
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance of Salmonella spp. and Staphylococcus aureus Isolated from Broiler Chicken Meat in Modern and Traditional Slaughterhouses of Morocco

Abstract: Handling and consuming contaminated meat can lead to food poisoning and the acquisition of antibiotic resistance genes. Staphylococcus aureus (S. aureus) and Salmonella spp. are the most isolated bacteria from broiler chicken meat, leading to serious foodborne diseases. The present study aimed to evaluate the presence and antibiogram profiles of Salmonella spp. and S. aureus strains in poultry meat purchased from modern and traditional poultry slaughterhouses in Morocco. Foodborne pathogens, such as Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…While the prevalence of Salmonella spp. and S. aureus obtained in this study (Table 1) is lower than that reported for poultry meat in Cambodia 17) , Egypt 18) , India 19) , Morocco 20) , and Thailand 21) the noncompliance of Salmonella spp. in poultry meat processing plants requires attention.…”
Section: Resultscontrasting
confidence: 74%
“…While the prevalence of Salmonella spp. and S. aureus obtained in this study (Table 1) is lower than that reported for poultry meat in Cambodia 17) , Egypt 18) , India 19) , Morocco 20) , and Thailand 21) the noncompliance of Salmonella spp. in poultry meat processing plants requires attention.…”
Section: Resultscontrasting
confidence: 74%
“…Salmonella has been the primary cause of the foodborne salmonellosis pandemic in humans over the last 20 years, during which egg products were the most often identified vehicle of the infection (Moosavy et al, 2015;Long et al, 2017). Over the past decades, the improper and uncontrolled use of antibiotics has allowed the appearance of strains of Salmonella with multiple drug resistance in many countries (Ben Salem et al, 2012;Nacer et al, 2022;Samy et al, 2022). For that reason, the antimicrobial resistance of Salmonella has become a matter of concern worldwide due to the significant threat that can present to public health (Wu and Hulme, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Formal slaughterhouses are government-approved facilities that adhere to strict animal welfare, hygiene, and food safety standards. Using these systems ensures humane treatment of animals and minimizes contamination risks [ 54 ]. Many low-income countries, including Jordan, have informal slaughter facilities known as backyard or unregulated slaughterhouses.…”
Section: Discussionmentioning
confidence: 99%